PERKEMBANGAN POPULASI TIKUS SAWAH PADA LAHAN SAWAH IRIGASI DALAM POLA INDEKS PERTANAMAN PADI 300 - Sudarmaji, Sudarmaji (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
As the main pest in rice crop, the rice field rats have to be controlled to anticipate yield loss. A specific study was conducted in ICRR field station in the period of August 2007-August 2008 within a 150 ha of intensified cropping area. The aim of this research was to study the population growth of the rice field rat in this intensified cropping system. The planting date was scheduled in such a way, so there will be three times of harvesting within a year.Â  Rat population sampling was performed by using Trap Barrier System (TBS) and Linear Trap Barrier System (LTBS). Seven units of TBS (25 m x 25 m) were set randomly either in their main habitats or the edge of the rice cropping area. A single unit of 10,000 m LTBS supported with 150 traps was erected surrounding all through the area. A regular daily counting was done to estimate the rat population based on the number of rat captured from TBS and LTBS. The level of rat damage and yield loss were other variables have been recorded. The results depicted that there was a significant increase of rat population growth which started from the first planting season through the next seasons (Planting season-2 and planting season-3). The rat captured from TBS increased significantly from 224 individuals during the planting season-1 to 492 and 677 animals during the next two planting seasons, respectively. The same figures were also performed from the rat captured from the LTBS, which increased from 429 rats in the plating season-1 to 1,423 and 1,733 individuals in the planting season-2 and 3, respectively. Rat attack within the three planting seasons were classified as light damage (<20%) and the average of rice yield was around 5.54-7.83 t/ha.